PTH-050 PEXACT®: analysis of 319 procedures performed at the Digestive Diseases Unit, University Hospital Aintree. (23rd September 2015) - Ahmed, S; Bowering, K; Polavarapu, N; Nicholson, R; Thomas, P; Sturgess, R
Abstract : Introduction: Patients with head and neck cancers can require nutritional support during and after treatment of their cancers. This is commonly done via a gastrostomy. The original "pull though" PEG has an increased risk of tumour implantation at the PEG site. We therefore changed our practice to direct puncture gastrostomy insertion in 2004, using the PEXACT® (fresenius) gastrostomy system, for all head and neck cancer patients. We have previously reported our first year experience of 89 cases. We report our practice since then. Methods: All PEXACTS® performed in the unit between November 2005 and November 2009 were identified, using our endoscopy reporting system and from referral register. Further information regarding each patient (readmissions, complications and mortality) was obtained from the hospital patient administration system. Results: According to the data available to date, 319 PEXACT® insertions were identified in 317 patients. 79% of patients were male (n=251). Average age was 58 years (18–85 years). 99% (n=316) patients had a head and neck cancer as the indication. Insertion was successful in 99% (n=316) and unsuccessful in 3(0.9%) patients: 2 cases due to poor access and 1 case due to gastric intramucosal haematoma. All patients had prophylactic antibiotics on the ward prior to the procedure. In total six patients died within 30 days (1.9%), 1 within 7 days (0.3%). Of the 30-day deaths, 3 were due to disease progression, one neutropenic sepsis following chemotherapy and two had no record of the cause of death available. Two patients had major procedure related complications (0.6%). On both occasions complications was identified immediately. One of the patients had splenic injury during the procedure and required emergency surgery, the second patient had intra-abdominal haematoma due to laceration of gastric wall which was managed conservatively and resolved spontaneously with good outcome. Ten (3.1%) patients had unplanned admissions within 30 days of their procedure. Four patients were admitted within 7 days (1.3%). Reasons for readmission included displaced or blocked gastrostomy tube n=2 (0.6%), disease progression n=2 (0.6%), gastrostomy site infection n=3 (0.9%) and 1 (0.3%) patient developed an aspiration pneumonia secondary to alcohol excess. There have been no cases of tumour implantation to date. Late displacement of the gastrostomy tube (>30 days after insertion) was common (6.6%). Most were replaced at the bedside. Conclusion: PEXACT® is a safe and reliable method of gastrostomy tube placement. Overall, our complication rate has fallen, with only two major procedure related complications during this period. There have been no procedure related deaths. There have been no cases of tumour implantation.